2013
DOI: 10.1016/j.bmc.2013.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of l- and d-phenylalanine derived rhodanines with novel C5-arylidenes as inhibitors of HCV NS5B polymerase

Abstract: Hepatitis C virus (HCV) NS5B polymerase is a key target for anti-HCV therapeutics development. Herein, we report the synthesis and in vitro evaluation of anti-NS5B polymerase activity of a molecular hybrid of our previously reported lead compounds 1 (IC50 = 7.7 µM) and 2 (IC50 = 10.6 µM) as represented by hybrid compound 27 (IC50 = 6.7 µM). We have explored the optimal substituents on the terminal phenyl ring of the 3-phenoxybenzylidene moiety in 27, by generating a set of six analogs. This resulted in the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The antiviral N-acylpyrolidine library (92 & 93) afforded clinical candidate (94) against HCV infections were discovered by HTS screening. The HTS assay against HCV NS5B polymerase identified a series of rhodanine analogues (95, 96 and 96e1) as promising antiviral agents and optimized by having chloro substitutions as essential for efficiency [71]. The benzodiazepine antipsychotic scaffold (97 to 99) targeting NS5B polymerase was scrutinized via SBBD platform and experimented as anti-HCV agents.…”
Section: Nucleoside Non-nucleoside and Protease Inhibitors As Anti-hmentioning
confidence: 99%
“…The antiviral N-acylpyrolidine library (92 & 93) afforded clinical candidate (94) against HCV infections were discovered by HTS screening. The HTS assay against HCV NS5B polymerase identified a series of rhodanine analogues (95, 96 and 96e1) as promising antiviral agents and optimized by having chloro substitutions as essential for efficiency [71]. The benzodiazepine antipsychotic scaffold (97 to 99) targeting NS5B polymerase was scrutinized via SBBD platform and experimented as anti-HCV agents.…”
Section: Nucleoside Non-nucleoside and Protease Inhibitors As Anti-hmentioning
confidence: 99%
“…The syntheses of compounds 1 and 4 – 6 [ 3 ] and 2 , 3 and 7 [ 1 ] was previously reported by our group and that for compounds 8 – 10 is reported herein (see Supporting Information ). LogP and LogS were predicted for all the compounds to assess their lipophilicity and water solubility using QikProp, version 4.8, Schrödinger, LLC, NY.…”
Section: Methodsmentioning
confidence: 92%
“…Recently, we synthesized compounds known as rhodanines and determined their efficacy in vitro against various MRSA strains [ 1 , 3 ]. Our results indicated that certain rhodanine derivatives were efficacious against six clinically relevant MRSA strains [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al [40] have reported the synthesis and in vitro evaluation of anti-NS5B polymerase activity of some novel rhodanine derivatives. Depending on the nature of substituents, the tested compounds exhibited IC 50 values ranging between 2 and 50 µM against NS5B polymerase.…”
Section: (Xxxvi)mentioning
confidence: 99%